Estrutura trófica da assembleia de peixes de dois riachos neotropicais : efeitos da urbanização em escala regional e local. - Tófoli, Raffael Marcos (2011)
The radial and accelerated expansion of urbanization leads to habitat degradation, with consequences on natural resources and aquatic ecosystems. In this way, this study aimed to identify whether the trophic structure of the fish fauna from two streams, Romeira (rural) and Nazaré (urban), allow us to infer about the conservation status of them, on a regional (two streams) and a local (longitudinal profile of each stream) scale. It was considered the data set from specific composition, numerical abundance and trophic group biomass. Both streams are located in Maringá (PR) and belong to Pirapó river sub-basin, Paraná river basin, Brazil. The fishes were sampled bimonthly between July 2007 and June 2008, in three distinct stations, represented by head, middle region and the mouth of the streams. Ten species were captured and through diet analysis and an exploratory analysis (DCA), six trophic groups were defined: omnivores, invertivores, invertivores/detritivores, deitritivores, insectivorous and piscivorous. Considering specific composition, the omnivores and invertivores stood out in Romeira stream and the detritivores in Nazaré stream. The numeric abundance was expressively represented by invertivores/detritivores, mainly in the head of both streams and was only represented by Poecilia reticulata. However, the grouping analysis (Euclidian distance) showed that the streams segregate regarding this attribute, but the differences was not significant (p = 0,183; ANOVA one-way null model). On the other hand, the biomass followed a similar trend to the abundance, nevertheless showed inverse relation regarding the invertivores/detritivores which were the less representative, highlighting the omnivores and detritivores. The grouping analysis showed that the streams did not segregated, which was corroborated by the ANOVA one-way null model, which did not detected significant difference (p = 0,184). The absence of clear and distinct patterns suggests the need of a larger number of replica, as well as allow to infer that the trophic structure was not a good tool for assessing the impacts of the environments.